Analysis of Stock Prices and Profitability Level in the Before and After the Covid-19 Pandemic (Case Study PT. Garuda Indonesia) - Purba, Rahima Br; Nasution, Herlina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to determine and analyze whether there are significant differences in stock prices and profitability levels before and after the announcement of the Covid-19 Pandemic case in Indonesia at PT. Garuda Indonesia, Tbk. the first to third quarters of 2019 and 2020. The type of data used is quantitative data in the form of daily closing prices (closing prices) and profitability ratios measured by Net Profit Margin (NPM), Return On Assets (ROA), and Return On Equity (ROE) for the first to the third quarter of 2019 and 2020, the data source is secondary data obtained from the Indonesia Stock Exchange (IDX) and the official website of PT. Garuda Indonesia, Tbk. namely www.garuda-indonesia.com. The analytical tool used to prove the hypothesis in this study is the paired sample t-test, which was previously tested for normality using SPSS.16. The results of this study indicate that there is no significant difference in stock prices and profitability levels as measured by Net Profit Margin (NPM), Return On Assets (ROA), and Return On Equity (ROE) between before and after the announcement of the Covid-19 pandemic.